Multi-Sensor Object Detection for Autonomous Driving - Asvadi, Alireza (2018)
Thesis submitted to the Department of Electrical and Computer Engineering of the Faculty of Science and Technology of the University of Coimbra in partial fulfillment of the requirements for the Degree of Doctor of Philosophy